Otentisitas Akta Yang Dibuat Oleh Pejabat Pembuat Akta Tanah (PPAT) Ditinjau Dari Perspektif Hukum Perdata - Zaenal Arifin Dilaga (Fakultas Hukum Universitas Mataram, 2011)
Authentic official document as the prima-facie evidence instrument has important role in each legal relation at social life, either in business relation, banking activity, land affair, social activity, and so on. The necessary on written evidence such as authentic document is more increase in line with the need progress of legal certainty in several economic and relations either in national, regional or local level. PPAT is as General Official that provided an authority to make the authentic documents of certain legal deed about rights of land or the owner rights of condominium unit. The authority is provided according to Government Regulation Number 37 Year 1998 about Occupation Regulation of PPAT (Making Official of Land Document). But recently, it has been happened the most interesting controversy when to be issued the Acts Number 30 Year 2004 about Notary occupation, because in the acts is decelerated that notary as a general official that has authority to make the authentic document and he other authorities such as regulated in this acts. The other authorities consist of authority of making document that related to land affairs. The big question, what is authentically of land document that is made by the notary. This article explains as compendiously about how to authentically of land document that to be made by PPAT.